Math smarts : tips for learning, using, and remembering math! - Long, Lynette; McGuinness, Tracy (Middleton, WI : Pleasant Company, 2004)
Describes the importance of mathematics in everyday life and offers advice on how to make learning math skills easier.
"American girl library."
Keywords: Arithmetic -- Juvenile literature; Arithmetic